The Concept of Jami’al Quran and the History of Jami’al Quran During the Time of the Prophet, the Rightly Guided Caliphs, and Thereafter - IKBAL, ACH FARIQUL (Maliki Interdisciplinary Journal, 2026)
The history of Jam'al Qur'an (collection of the Qur'an) is a crucial stage in the development of Islam that has a significant impact on the needs and beliefs of Muslims. Procedures This began in the time of the Prophet Muhammad (saw), when the text was written by the companions in various simple mediums, such as date palm fronds, bones, and skin, and then translated by the memorizer (huffaz). Following the Prophet's death, a thorough study of the Qur'an was conducted during the time of Caliph Abu Bakr ash-Siddiq at the suggestion of Umar bin Khattab, especially after numerous studies of the Qur'an fell in the Yamamah War. Zaid bin Thabit oversaw this codification, which produced mushaf that was collected in a single unit. During the time of Caliph Utsman bin Affan, Mushaf copying and reading standardization were carried out to identify the differences in Qira'at throughout various Islamic countries. Ottoman Mushaf. This study aims to clarify the meaning of the Qur'anic text and analyze its implications for the interpretation of the Qur'an and the development of the Islamic legal system. It can be inferred from the historical-normative perspective that the process of codifying the Qur'an demonstrates the widespread awareness of the validity of Islamic law, which strengthens the Qur'an as the primary source of Islamic law that is authoritative and has been upheld up to this point.